STRATEGIC ENHANCEMENT OF FINANCIAL RISK MANAGEMENT SYSTEMS IN MODERN ENTERPRISES (American Journal of Business Management, Economics and Banking, 2026)
This article is dedicated to the issues of improving the financial risk management system in modern enterprises. The research analyzes the role of digital technologies, predictive analytics, and internal control mechanisms in ensuring financial stability. The article proposes strategies for transitioning from traditional approaches to a proactive and integrated risk management system, highlighting the interconnection between mathematical models and corporate governance culture.